TECHNIQUES IN TEACHING READING AND WRITING THAI BRAILLE TO VISUALLY IMPAIRED KINDERGARTEN 3 STUDENTS (Proceedings of International Conference on Special Education, 2017)
This paper explores on different teaching techniques and materials I use to teach reading and writing to beginning-level learners at Kindergarten 3 with almost zero reading and writing skills in Thai Braille. Before teaching them how to read Thai Braille, these students had already gone through the Pre-Braille stage and have memorized the Braille codes. However, they have not experienced the tactile form of the Thai alphabet at this stage yet. Before proceeding to reading, the students were taught about the basics of navigating the book such as locating the page number and the hand movement when reading the Braille text on the book. They were also taught the basics of writing Braille such as the proper way of holding the stylus and navigating the slate before giving the first writing task. To aid their learning and make it interesting for them, I created four Braille textbooks tailored according to my techniques in teaching reading and writing Thai Braille to beginners. The textbooks focus more on reading but writing Thai Braille is also integrated. The first textbook is used for students to identify the target letter among other letters in a sentence. The teacher read the sentences while guiding the hand of the student to trace the sentence in Braille. The teacher then asks the blind students to look for the target letter in the sentence. This gives a thrill to the blind students. They get so excited to hunt the letters in sentences. The second textbook has pairs of consonants and the students are asked to look for the target consonant. The 3rd textbook is about combining Thai consonants with Thai vowels. The 4th textbook has basic words used in daily conversation. Most of these are five-letter words. CFBT Educational Technological Center for the Blind (ETCB) had included helpful marks in printing the textbooks. One of these is enclosing the group of words or sentences in a box made of dots. To make learning fun, I named each box after a student, an animal or anything that can make learning interesting for the students. Fun activities like guessing games and group work to encourage cooperative learning were also integrated to make learning more engaging for the blind students. After using these techniques, I have observed that the blind students get excited to read whenever they have a book on their hand. CFBT Educational Technological Center for the Blind (ETCB) has also produced handy books (210mm x 148.5mm) for KG3 blind students to easily carry around. The combination of these teaching techniques and effective materials for learning enables our KG 3 blind students to read and write in Thai Braille and creates a culture of reading among them.